Law Enforcement Against Building Permit Violatins In Semarang City (Case Study: Gunungpati District) - Aprylia Putri Kusumawati (Faculty of Law, Universitas Negeri Semarang, 2025)
This research aims to analyze the types of building permit violations, the law enforcement process, and the obstacles faced in implementing legal measures in Gunungpati District, Semarang City. The study employs an empirical juridical approach, using data collection techniques such as interviews, observations, and document analysis. The findings indicate that the most common violations include construction without permits, unauthorized changes in building function, breaches of the building setback line (GSB), and violations of building height and density regulations. Legal enforcement has primarily involved administrative steps such as issuing warning letters; however, these measures have not been fully effective due to various obstacles, including a shortage of supervisory personnel, low public legal awareness, and insufficient outreach regarding the online building permit system (SIMBG). The study recommends enhanced inter-agency coordination, strengthening of human resources, and public education to promote legal compliance and sustainable spatial planning.